2010
DOI: 10.1007/s00726-010-0517-3
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun strategy-based proteome profiling analysis on the head of silkworm Bombyx mori

Abstract: Insect head is comprised of important sensory systems to communicate with internal and external environment and endocrine organs such as brain and corpus allatum to regulate insect growth and development. To comprehensively understand how all these components act and interact within the head, it is necessary to investigate their molecular basis at protein level. Here, the spectra of peptides digested from silkworm larval heads were obtained from liquid chromatography tandem mass spectrometry (LC-MS/MS) and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
0
27
1
Order By: Relevance
“…Here, a brief overview to appreciate the high innovation content taking into account the potential health implications: (i) LAB may improve the palatability of whole grain and fiber-rich products (Katina et al, 2005) associated with health benefits, such as enhanced regulation of blood glucose levels, reduced risk of diabetes, cardiovascular disease, and certain cancers (Jacobs et al, 1998; Liu et al, 2000; Pereira et al, 2002); (ii) LAB may modify the bran fraction of the grain (rich in fiber) in such a way that larger amounts of bran can be utilized in breads (Katina et al, 2005); (iii) LAB may contribute to produce novel, naturally fermented health-oriented products enriched in gamma-aminobutyric acid (Li and Cao, 2010; Li et al, 2010); (iv) LAB may synthesize angiotensin I-converting enzyme (ACE)-inhibitory peptides (Rizzello et al, 2011); (v) LAB may produce non-digestible polysaccharides, or modify accessibility of the grain fiber complex to the gut microbiota (Poutanen et al, 2009; Garai-Ibabe et al, 2010; Elizaquível et al, 2011). …”
Section: Lab Biotechnological Potential In Pasta-makingmentioning
confidence: 99%
“…Here, a brief overview to appreciate the high innovation content taking into account the potential health implications: (i) LAB may improve the palatability of whole grain and fiber-rich products (Katina et al, 2005) associated with health benefits, such as enhanced regulation of blood glucose levels, reduced risk of diabetes, cardiovascular disease, and certain cancers (Jacobs et al, 1998; Liu et al, 2000; Pereira et al, 2002); (ii) LAB may modify the bran fraction of the grain (rich in fiber) in such a way that larger amounts of bran can be utilized in breads (Katina et al, 2005); (iii) LAB may contribute to produce novel, naturally fermented health-oriented products enriched in gamma-aminobutyric acid (Li and Cao, 2010; Li et al, 2010); (iv) LAB may synthesize angiotensin I-converting enzyme (ACE)-inhibitory peptides (Rizzello et al, 2011); (v) LAB may produce non-digestible polysaccharides, or modify accessibility of the grain fiber complex to the gut microbiota (Poutanen et al, 2009; Garai-Ibabe et al, 2010; Elizaquível et al, 2011). …”
Section: Lab Biotechnological Potential In Pasta-makingmentioning
confidence: 99%
“…We used iTRAQ isobaric-tag-labeled proteomics, coupled with two-dimensional LC-MS/MS, to identify proteins and quantitatively compare relative protein abundance in the heads of newly emerged diapause-destined and non-diapause-destined adult female cabbage beetles. The head of insects contains the brain, compound eyes, corpus allatum and other important parts of the nervous, sensory, and endocrine systems where environmental cues related to diapause are perceived and processed, as well as muscle and cells of the anterior fat body (Denlinger, 2002; Koštál, 2006; Li et al, 2010; Zhang et al, 2012). It remains unclear how environmental signals such as photoperiod, that are perceived by larvae during the diapause induction phase are stored and subsequently regulate the major molecular processes involved in diapause preparation in cabbage beetle adults (Wang et al, 2004), but we focus on the head because we expect that it plays a critical role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Other brain proteome studies have been conducted on the fleshfly Sarcophaga crassipalpis (Pavlides et al, 2011), aphid (Hummon et al, 2006;Huybrechts et al, 2010), the silkworm Bombyx mori (Li et al, 2007;Li et al, 2010;Li et al, 2009), and the honey bee (Uno et al, 2007;Wolschin et al, 2009). A differential proteomic study of diapausing and nondiapausing pupal brains of fleshfly have shown higher amounts of stress-related proteins but lower abundance of other metabolism-related brain proteins in the diapausal state (Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%